(untitled) (International Journal of Educational Management, Rivers State University., 2025)
The study examined the role of university administrators in enhancing lecturers’ performance towards sustainable development in public universities in Bayelsa State. Two Objectives, two research questions and two Hypotheses guided the study. A total of 166 university administrators (Deans, Directors and Head of departments) of public universities in Bayelsa State for 2023/2024 academic session made up the population and sample for the study. The instrument for the study was a questionnaire developed on a five-point rating scale ranging from very low extent to very high extent. Three experts in Educational management and Measurement and Evaluation validated the instrument and the instrument test of reliability using Cronbach Alpha method yielded a coefficient of 0.79 and 0.83 respectively for the two sections of the instrument. Mean rating was used to answer the research questions, while Z-test was used to test the hypotheses. It was revealed among others that there is no statistically significant difference between federal and state universities in terms of how administrators organize training and workshops to enhance lecturers’ performance towards sustainable development. Indicating that both types of institutions may be perceived similarly in their efforts to enhance lecturers’ performance towards sustainable development. Based on the findings, it was recommended inter-alia that universities should strengthen their efforts by introducing more tailored and innovative training programmes; which should focus on sustainable development practices and address specific challenges faced by lecturers to further improve their performance.